Evaluasi dari Kebijakan Pariwisata Geopark dan Strategi untuk Meningkatkan Jumlah Wisatawan yang Berkunjung ke Kabupaten Belitung - Leonandri, Dino Gustaf; Riau, Dwi Putranto; Listiani, Teni (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
The management, socialization and development of the Belitung Geopark is very significant. The increase in the number of visitors has a positive impact on revenue and operational costs. Therefore, policies and marketing must be improved. The aim of this research is to analyze the evaluation of Belitung Regency government policies in improving the tourism industry. Evaluating the efficiency of human resource management in the tourism industry in Belitung Regency. Evaluate the effectiveness of collaboration between institutions in improving tourist visit programs in Belitung Regency. Examining the facilities, infrastructure and technology developed to attract investor interest in Belitung Regency. Analyzing resource allocation for the development of the tourism sector to increase the number of tourist visits. Based on the research findings of Leo Agustino (2016) using a policy evaluation model which includes various factors such as Apparatus Resources (SDA), Institutions, Facilities, Infrastructure, Technology, Finance and Supporting Regulations, the researcher concluded that evaluating regulatory implementation policies in Belitung Regency No. . 12 of 2015 and Regent Regulation no. 10 of 2019. Keywords: evaluation, tourism policy, competitiveness